RESPONS PRODUKTIVITAS RUMPUT PAKCHONG TERHADAP APLIKASI PUPUK KANDANG AYAM DAN SAPI BERDASARKAN PRODUKSI BERAT SEGAR, BERAT KERING, DAN BERAT KERING PER HEKTAR - Rizhad Baginda Hakim Ohorella; Insun Sangadji; Marna Eoh; Shirley Fredriksz (MARSEGU : Jurnal Sains dan Teknologi, 2026)
Pakchong grass (Pennisetum purpureum × Pennisetum americanum) is one of the superior forages with high productivity potential; however, its production is strongly influenced by soil fertility and fertilization management. This study aimed to evaluate the productivity response of Pakchong grass to the application of chicken manure and cattle manure based on fresh weight production, dry weight production, and dry weight yield per hectare. The study employed a Completely Randomized Design (CRD) consisting of three treatments with five replications: without fertilizer (P0), chicken manure (P1), and cattle manure (P2). The observed variables included fresh weight production, and dry weight production, and dry weight production per hectare. Data were analyzed using Analysis of Variance (ANOVA). The results showed that the application of chicken manure and cattle manure significantly affected (P<0.05) all observed parameters. The highest fresh weight production was obtained in treatment P1 at 1.152 ± 0.239 kg, followed by P2 at 0.894 ± 0.287 kg, and P0 at 0.585 ± 0.153 kg. Similarly, the highest dry weight production was recorded in P1 at 0.1260 ± 0.0277 kg, followed by P2 at 0.1072 ± 0.0376 kg, and P0 at 0.0738 ± 0.0154 kg. The highest dry weight per hectare was also observed in P1 at 224.07 ± 49.03 kg/ha, followed by P2 at 190.72 ± 66.87 kg/ha, and P0 at 131.01 ± 28.31 kg/ha. It can be concluded that chicken manure application produced the best response in improving Pakchong grass productivity compared with cattle manure and no fertilizer application.